Navigating the Legal Landscape of Cybersecurity Regulation in Lithuania - Juknevičiūtė, Ugnė; Murachov, Vladyslav (Vilnius University Open Series, 2024)
This article provides a detailed assessment of legislative cybersecurity issues and challenges that Lithuanian authorities are facing and might face in the future. To achieve this purpose, Lithuanian cybersecurity legislation is evaluated and compared with European Union law. This study draws attention to and assesses the problematic aspects related to cybersecurity regulation. After analysing all sources, it can be concluded that Lithuania needs to improve its legal instruments to ensure that they are robust, adaptable and in line with new cybersecurity threats and technological advances because cybercrime remains a persistent issue. The balance between security and privacy, flexibility and capabilities of entities and individuals must be maintained. The Republic of Lithuania law on Cyber Security and The National Cyber Security Strategy sets out the main guidelines to ensure the prevention and investigation of cybercrime. Even though from a theoretical point of view, it seems that the law adjusted the aims of risk management, the organisational and technical requirements for cybersecurity and Cyber Security Strategy sets out the main objectives for the country’s cybersecurity efforts, both in the public and private sectors. But on the practical part, the picture is completely different.